Pengaruh Kegiatan Ekstrakurikuler Keagamaan dan Non Keagamaan Terhadap Pembentukan Karakter Siswa di MA Muhammadiyah 1 Jember - Huluq, Shella Amy Niar (Jurnal Al-Fikrah, 2022)
School is one of the factors that can influence the formation of student character through extracurricular activities. The learning process in schools does not only rely on curricular or intracurricular activities. But it must also be supported by developmental activities carried out outside the classroom such as extracurricular activities that lead to the formation of student character in schools. In an effort to shape the character of students, schools also need to hold religious and non-religious extracurricular activities because in these activities there are educational values that can be used as references by students so that students can be trained and more focused on doing more positive things so that students can avoid despicable character. The purpose of this study is to find out whether there is an influence of religious and non-religious extracurricular activities on the formation of student character, in this study using quantitative research methods with this research data using questionnaires the subjects of this study were class X and XI students who actively participated in religious and non-religious extracurricular activities totaling 62 respondents. The results of this study show that religious and non-religious extracurricular activities have a partial and simultaneous influence on the character of students known by the results of testing multiple linear regression theory with a simultaneous value of R value = 0.249 which means that the value of the influence of religious and non-religious extracurricular activities on the formation of student character in MA Muhammadiyah 1 Jember is 24.9% as for partially each activity variable religious extracurricular activities on student characters are known to be 0.294 or 29.4% while in the second variable, namely non-religious extracurricular activities, it affects the character of known students with a score of 0.352 if presented in percent, it is 35.2%. The conclusions of the study prove that religious and non-religious extracurricular activities are closely interrelated in the formation of student character.